2020
DOI: 10.1101/2020.11.26.399725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial heterogeneity of glioblastoma cells reveals sensitivity to NAD+ depletion at tumor edge

Abstract: Even after total resection of glioblastoma core lesions by surgery and aggressive post-surgical treatments, life-threatening tumors inevitably recur. A characteristic obstacle in effective treatment is high intratumoral heterogeneity, both longitudinally and spatially. Recurrence occurs predominantly at the brain parenchyma-tumor core interface, a region termed tumor edge. Given the difficulty of accessing it surgically, the composition of the tumor edge, harboring both cancerous and non-cancerous cells, remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In addition, this metabolic alteration is characterised by an increase in the ratio of oxidised and reduced forms of the carrier molecule Nicotinamide adenine dinucleotide (NAD+/NADH) [39, 40]. Yamashita et al showed this ratio is higher at the core of GBM tumours than the periphery [41], implying a shift to aerobic glycolysis in the tumour core. Interestingly however, the assuming less proliferative cell lines (non-fluorescent tumour margins), while they were more sensitive to Gboxin, their proliferation was not disturbed by the drug in culture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this metabolic alteration is characterised by an increase in the ratio of oxidised and reduced forms of the carrier molecule Nicotinamide adenine dinucleotide (NAD+/NADH) [39, 40]. Yamashita et al showed this ratio is higher at the core of GBM tumours than the periphery [41], implying a shift to aerobic glycolysis in the tumour core. Interestingly however, the assuming less proliferative cell lines (non-fluorescent tumour margins), while they were more sensitive to Gboxin, their proliferation was not disturbed by the drug in culture.…”
Section: Discussionmentioning
confidence: 99%